Analisis Usaha Pengolahan Ikan Teri (Stolephorus heterolobus) di Desa Bunsur Kecamatan Sungai Apit Kabupaten Siak Provinsi Riau - Sri Mahfuza; Zulkarnaini; Tince Sofyani (JURNAL SOSIAL EKONOMI PESISIR, 2022)
This research was conducted from 30 July to 10 September 2019 in Bunsur Village, Sungai Apit District, Siak Regency, Riau Province. The research objective is to calculate the amount of investment, analyze the amount of production costs, revenues and profits and to analyze the business feasibility in Bunsur Village. The method used was a survey method with 16 fishermen as respondents. The result of the research is that the average total investment of anchovies processing fishermen business in Bunsur Village, Sungai Apit District, Siak Regency is IDR. 28.632.062,50. The average total cost of anchovy in 1 period is IDR. 857.463,72 for the average total cost of anchovies business in 1 month, namely IDR. 1.714.927,43 while the average total cost of anchovies 1 year is IDR. 20.579.129,19. The average total revenue or gross income is IDR. 2.222.187,50/period, for the average monthly gross income of IDR. 4.444.375,00/month and for the average annual gross income of IDR. 53.332.500,00/year while the total profit or average net income obtained by anchovy processing fishermen is IDR. 1.364.723,78/period and for the average monthly gross income of IDR. 2.729.447,57/month while the average gross income for the period was IDR. 32.753.370,81/year. Analysis of the feasibility of anchovies processing business in Bunsur Village, Sungai Apit District, Siak Regency, obtained RCR values, namely (2,59), FRR (115,42) and PPC values (0,89), which means that the effort to control anchovy in Bunsur Village is feasible for next.